Neural basis for processing hidden complexity indexed by small and finite clauses in Mandarin Chinese - Ansaldo, Umberto; Lai, Jackie; Jia, Fanlu; Siok, Wai Ting; Tan, Li Hai; Matthews, Stephen (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study we investigate how the human brain processes small clauses and finite clauses. Small clauses are instances of ‘simpler’ syntax in the sense that they do not involve operations such as Move and Tense, and have been argued to represent an earlier stage of syntactic evolution before the development of fully-fledged syntax (Bickerton, 1990; Jackendoff 2010; Uriagereka, 2008). Understanding how the brain processes instances of different levels of syntactic complexity may further our understanding of (i) the analytical functions of specific brain regions, and (ii) the distribution of labor in the interpretation or different levels of syntax. To pursue this hypothesis, we ask whether small clauses require different analytical processes than regular syntax. This report provides evidence that they do. In an fMRI study of syntactic processing in a group of Mandarin speakers, small clauses showed greater activation of areas involved in semantic processing. In addition, both small and finite clauses showed substantial activation of areas implicated in syntactic and semantic processing, including significant RH activation. We interpret these findings with reference to Levinson’s articulatory bottleneck: structures which appear simpler in terms of syntactic production may require more effort in parsing.